Islamisasi dan Syariatisasi Samudera-Pasai Abad ke-14 Masehi - Ayang Utriza Yakin (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
This article discusses the process of Islamization and shariahization in Samudera Pasai. Pasai was the first region to be islamized by those who spread Islam from Arabian peninsula. From this region Islam spread throughout Nusantara. Pasai played an important role in Islamizing Nusantara. Based on local and foreign sources as well as the historiography of Pasai, this article tries to elaborate the process of Islamization of Samudera Pasai comprehensively. In terms of shariahization, it is meant as an endeavor to implement Islamic law which was initially identical with Islamization. Based on Ibn Bat?tah, a Moroccon traveller, who visited Pasai, it is apparent that some aspects of Islamic law had been implemented and constituted as an integral part of societal and political life in this Muslim kingdom. This article shows that Islamic law had been practiced from the beginning as it went hand in hand with the process of Islamization.